Antiangiogenesis-Combined Photothermal Therapy in the Second Near-Infrared Window at Laser Powers Below the Skin Tolerance Threshold - Chen, Jian‑Li; Zhang, Han; Huang, Xue‑Qin; Wan, Hong‑Ye; Li, Jie; Fan, Xing‑Xing; Luo, Kathy Qian; Wang, Jinhua; Zhu, Xiao‑Ming; Wang, Jianfang (Nano-Micro Letters, 2019)
Photothermal agents with strong light absorption in the second near-infrared (NIR-II) region (1000–1350 nm) are strongly desired for successful photothermal therapy (PTT). In this work, titania-coated Au nanobipyramids (NBP@TiO2) with a strong plasmon resonance in the NIR-II window were synthesized. The NBP@TiO2 nanostructures have a high photothermal conversion efficiency of (93.3 ± 5.2)% under 1064-nm laser irradiation. They are also capable for loading an anticancer drug combretastatin A-4 phosphate (CA4P). In vitro PTT studies reveal that 1064-nm laser irradiation can efficiently ablate human lung cancer A549 cells and enhance the anticancer effect of CA4P. Moreover, the CA4P-loaded NBP@TiO2 nanostructures combined with PTT induce a synergistic antiangiogenesis effect. In vivo studies show that such CA4P-loaded NBP@TiO2 nanostructures under mild 1064-nm laser irradiation at an optical power density of 0.4 W cm−2, which is lower than the skin tolerance threshold value, exhibit a superior antitumor effect. This work presents not only the development of the NBP@TiO2 nanostructures as a novel photothermal agent responsive in the NIR-II window but also a unique combined chemo-photothermal therapy strategy for cancer therapy. Highlights: 1 Titania-coated Au nanobipyramids (NBP@TiO2) with a high photothermal conversion efficiency in the NIR-II window are synthesized. 2 The TiO2 shell is capable for the loading of the anticancer drug combretastatin A-4 phosphate (CA4P). 3 The CA4P-loaded NBP@TiO2 nanostructures subjected with photothermal therapy induce synergistic anticancer and antiangiogenesis effects under 1064-nm laser irradiation at a power density lower than the skin tolerance threshold value.